A ação efetiva do Conselho Municipal dos Direitos da Criança e do Adolescente (CMDCA) de Toledo/PR: vinculação e prioridade - Dias, Rodrigo Rodrigues (2012)
The research seeks to investigate the relationship between the effective action of the Management Councils, as spaces for democratic participation, and the issues of binding and priority through the Municipal Council for the Rights of the Child and Adolescent of the City of Toledo / PR, based on the administrations of 2007/2009 and 2009/2011. By effective action, we understand the one which includes the participation of civil society in the debates, proposals and preparation of decisions about public policies in the municipal area of child and adolescent and seeks the means to enforce the substance of the decision by the municipal government. On the one hand, the binding, by legal and constitutional commandment, determines the inclusion, in public budgets, of the deliberated public policies by the Councils. On the other hand, there is also the prediction of priority attendance of the infantojuvenil demands, which must be accomplished by the actions of the Council, and reflects in the imposing of the deliberations. However, the reality of the Councils has shown that the Government has not converted the decisions in municipal public policies, which, in the area of Children and Youth, must be priority. Based on the analysis of the records in the course of two terms, we corroborate the explanation, formulated as initial working hypothesis, backed the Council's own behavior: the more effective is the Council's action, the more the Government will comply with their deliberations, including them in the budget and turning them into public policy.